Analysis Of Factors That Effect Lecturer Productivity Producing International Scientific Article In Private University: Motivation As A Moderating Variable - Andriani, Dewi; Purwana, Dedi; Susita, Dewi (IJHCM (International Journal of Human Capital Management), 2020)
In accordance with the demands facing global challenges, lecturers are one of the important factors for creating competent university graduates, and the main role of colleges/universities is teaching, research and community service and directed to expand knowledge and open new avenues of science and technology. The purpose of this study is to analyze the factors that affect the productivity of lecturers producing international scientific article in Private Universities by using the Structural Equation Modeling. The data used are primary data by conducting surveys with a total of 310 respondents, and the analysis used includes validity, reliability, multiple linear regression, sobel tests, and hypothesis testing. The results showed that the positive direct effect of Reward System, Transformational Leadership Style, Communication and Motivation on Lecturer Productivity. Furthermore. From the four exogenous variables, Communication proved to be the most dominant influence on Productivity, amounting to 5,132, and also the results of the study showed that the positive indirect effect through Motivation was a moderating variable.